The 2nd Euro-Asian Congress of Pharmacoepidemiology: Non-Communicable Diseases as a Threat to Sustainable Development - Nazila Yousefi; Farzad Peiravian (Tehran University of Medical Sciences, 2023)
The 2nd Euro-Asian congress of pharmacoepidemiology (EAPEC 2019) was held in Tehran, Iran, November 13rd-15th, 2019[1]. The congress was organized by the school of pharmacy of Shahid Beheshti University of Medical Sciences (SMBU), and supported by Iran Food and Drug Administration (IFDA) as well as a number of medical universities, research centers, and pharmaceutical companies. This editorial includes more infornation about this congress.